2014
DOI: 10.1177/1477370814525935
|View full text |Cite
|
Sign up to set email alerts
|

From legalist to Dirty Harry: Police recruits’ attitudes towards non-legalistic police practice

Abstract: This study provides a test of the presumption that police recruits with a diverse background, undertaking comparatively long academic training, will refrain from non-legalistic practices. This is tested by longitudinal survey data, covering two cohorts of Swedish police recruits. The results show stable support for the legalistic perspective during academy training. However, during on-the-job training, the recruits become more positive towards non-legalistic practices. This reorientation takes place quite irre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 25 publications
(45 reference statements)
3
25
0
7
Order By: Relevance
“…Our finding of a divided group of police students is in line with other recent Scandinavian studies on police students' and officers' attitudes (Fekjaer et al, 2014;Petersson, forthcoming). We found differences between the students when it came to attitudes towards the role of the police and career plans, and these attitudes influenced their opinions of police armament.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Our finding of a divided group of police students is in line with other recent Scandinavian studies on police students' and officers' attitudes (Fekjaer et al, 2014;Petersson, forthcoming). We found differences between the students when it came to attitudes towards the role of the police and career plans, and these attitudes influenced their opinions of police armament.…”
Section: Resultssupporting
confidence: 81%
“…Since previous research has indicated that autonomous attitudes are more wide-spread among officers working the streets (Fekjaer, Petersson, & Thomassen, 2014), we expect that those oriented towards a career in operational police work would have more positive attitudes towards armament.…”
Section: Previous Research and Theoretical Backgroundmentioning
confidence: 99%
“…Et indirekte bilde av kultur kan ses i undersøkelser som studerer samme deltagere over tid. En slik undersøkelse av svenske politistudenter så på hvilke vurderinger som ligger til grunn for bruken av politiets fullmakter med hensyn til inngripen (Fekjaer, Petersson, & Thomassen, 2014). Funnene viste at politistudentene i starten av utdanningen ga uttrykk for sterke legale holdninger.…”
unclassified
“…klaringer og teorier (Fekjaer, Peterson, & Thomassen, 2014;Lagestad, 2010;Larsson, 2010;Larsson, Strype, & Thomassen, 2006;Lauritz, 2009;Winnaess & Helland, 2014). Disse studiene bidrar til en bedre forståelse av sammenhengen mellom sosiale strukturer, kulturer og politiarbeidet som et sosialt fenomen.…”
unclassified
“…Flere studier viser hvordan politibetjenter kan ha lett for å fokusere på seg selv eller sin egen interesse i situasjonen (Haugland, 2015;Fekjaer, Peterson, & Thomassen, 2014;Lagestad & Rønning, 2010). For eksempel skriver Haugland (2015, s. 70-71) at det er mye som tyder på at betjentenes fokus i et politioppdrag ikke er på situasjonen og menneskene involvert, men på deres egne behov: «Skjønnet bar preg av fokus på egensikkerhet, verstefallsteorier og behovet for å ha full kontroll.» Selv om evnen til dømmekraft ikke direkte kan laeres gjennom pensumstudier ved utdanningen, kan dette aspektet ved praksis ikke unngås eller overses, for da kan vi ende opp med et stivnet politiskjønn slik Haugland (2015, s. 70) beskriver det, og konsekvensen kan vaere at politiet ikke møter mennesket på oppdraget.…”
unclassified